The Effect of Different Drying Methods and Slice Thickness on The Quality of Porang (Amorphophallus Muelleri) Chips - Bambang Sigit Amanto; Hanun O. Chairunisa; Sigit Prabawa; Kawiji; Bara Yudhistira (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2023)
Porang (Amorphophallus muelleri) is a type of tuber that has a high glucomannan content. The purpose of this study was to determine the effect of slice thickness on the quality of porang tuber chips using the Green House Effect (GHE) method by pretreatment with 0.15% sodium metabisulfite solution immersion. The slice thickness treatment was carried out at three levels, including 4 mm, 6 mm, and 8 mm, while the drying treatment was carried out with two types, which are the GHE drying method and the conventional drying method using sunlight. The results of the research on porang chips on brightness, moisture content, glucomannan content, ash content, and calcium oxalate content showed that the thickness of the slices had an effect on the quality of the chips. The thicker the slices of the porang chips, the darker the color of the porang chips. The thicker the slices of the porang chips, the higher the water content of the chips. The amount of glucomannan (%) in porang chips goes down as the slices get bigger.